2019
DOI: 10.1111/are.14272
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary dehydrated lemon peel on some biochemical markers related to general metabolism, welfare and stress in gilthead seabream (Sparus aurataL.)

Abstract: Dehydrated lemon peel (DLP) at two levels (1.5% and 3%) was included for 30 days in the diet of gilthead seabream (Sparus aurata L.) and after 15 and 30 days the serum and skin mucus of fish were analysed. In serum, both experimental diets led to an initial decrease in glucose and lactate after which the levels became comparable to the control. Dietary DLP modulated the activity of transaminases, alanine aminotransferase and aspartate aminotransferase. The total antioxidant status showed a progressive increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
(174 reference statements)
0
6
0
Order By: Relevance
“…In fact, this protein is normally present at a low level in organisms with a good balance of antioxidants and over-expressed in a situation of oxidative stress [42][43][44]. Our previous study on the inclusion of dehydrated lemon peel in the diet for seabream showed a reduction of the HSP70 levels in fish fed on increased levels of bioactive compounds, due to the antioxidant composition of this resources, which is able to guarantee protection against oxidative stress [2]. Accordingly, Di Giancamillo et al [45] described a decrease of HSP70 in pigs fed a diet supplemented with a natural verbascoside extract, compared with pig fed a high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, this protein is normally present at a low level in organisms with a good balance of antioxidants and over-expressed in a situation of oxidative stress [42][43][44]. Our previous study on the inclusion of dehydrated lemon peel in the diet for seabream showed a reduction of the HSP70 levels in fish fed on increased levels of bioactive compounds, due to the antioxidant composition of this resources, which is able to guarantee protection against oxidative stress [2]. Accordingly, Di Giancamillo et al [45] described a decrease of HSP70 in pigs fed a diet supplemented with a natural verbascoside extract, compared with pig fed a high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…A growing amount of scientific evidence is demonstrating that supplementing diets with natural compounds that act as protective factors or immunostimulants can improve growth performance, product quality, fish health, and physiological response to stress situations and diseases [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that fish fed diets containing single‐use of B. licheniformis increased the antioxidant enzyme responses (Gobi et al, 2018). Dehydrated lemon peel in the diet increased the activity of the antioxidant enzymes in gilthead seabream (García Beltrán et al, 2019). However, Han et al (2015) reported that SOD activity was not significantly affected by B. licheniformis supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Lemon, Citrus aurantifolia is a polyembryonic plant cultivated in many countries all over the world (Enejoh et al, 2015). This plant has shown antibacterial, anthelmintic, antifungal, antiaflatoxigenic, anticancer, immunomodulatory, antiobesity, antihypertensive, and anti‐osteoporosis properties when applied in vivo and in vitro (García Beltrán et al, 2019; Pathirana, Wimalasena, De Silva, Hossain, & Heo, 2018). Studies conducted previously have shown that C. aurantifolia contains carbohydrates, sugar, soluble and insoluble fiber, sodium, vitamins (vitamin C), minerals, fatty acids, amino acids, saponins, alkaloids, tannins, phenolics, flavonoids, and terpenoids (Akinsete & Odeniyi, 2016; Al Namani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation